Pelaksanaan Hukum Bali’i Menurut Suku Dayak Lawangan Di Desa Ampah Kecamatan Dusun Tengah Kabupaten Barito Timur - budiarto santoso (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The writing of this article aims to collect and explain customary sanctions in the form of Bali'i Law on the Lawangan Dayak community to the general public. Resolution of problems with customary law has a positive impact on the community. Tradition circulating in society states that a cause will have an impact on life and relationships in the community. Orders of life and relationships become chaotic. Thus, this situation must be immediately neutralized by carrying out traditional rituals. The method used in this study is a qualitative descriptive method, namely a method that is able to provide an overview of the processes, events and events that occur factually and accurately regarding the phenomena that occur. The results of the study show that Balinese Law is one of the customary law norms that are still maintained by the Lawangan Dayak community. The implementation of Bali'i Law aims to provide sanctions to individuals who intentionally or unintentionally have injured or even resulted in the loss of a person's life. Bali'i law consists of Bali'i Bolum and Bali'i Mate. In general, the Lawangan Dayak people who live in the Kedamangan Paku Karau area do not know about the Bali'i Law. The role of traditional leaders and community leaders is highly expected for the sake of upholding these customary norms. Thus, it can be concluded that the implementation of Balinese law is very rare due to the lack of socialization and implementation and the absence of a special manual regarding these legal norms. Keywords: Law, Sanctions, Bali’i Law